Runtime testing approach of structural adaptations for dynamic and distributed systems. (2015) - Lahami, Mariam; Krichen, Moez; JmaÁ¯el, Mohamed
Adaptable and distributed component-based systems need to be checked and validated in order to ensure their correctness and trustworthiness when structural dynamic changes occur. Runtime testing, seen as an online validation technique, is used in this work for this aim. Indeed, we propose a generic and resource aware test platform that: 1) looks for a minimal set of tests to re-execute written in the TTCN-3 standard notation; 2) assigns the involved test components in execution nodes while respecting resources and connectivity constraints and finally; 3) performs runtime tests with reducing interference risks by supplying different test isolation strategies depending on testability degrees of each component under test. To show the relevance of our solution, a prototype is proposed and illustrated via a case study in the healthcare domain implemented using the OSGi platform.